Customising turnaround time indicators to requesting clinician: a 10-year study through balanced scorecard indicators. Issue 9 (25th June 2014) - Salinas, Maria; López-Garrigós, Maite; Santo-Quiles, Ana; Gutierrez, Mercedes; Lugo, Javier; Lillo, Rosa; Leiva-Salinas, Carlos
Abstract : Aim: The purpose of this study is, first to present a 10-year monitoring of postanalytical turnaround time (TAT) adapted to different clinicians and patient situations, second to evaluate and analyse the indicators results during that period of time, and finally to show a synthetic appropriate indicator to be included in the balanced scorecard management system. Methods: TAT indicator for routine samples was devised as the percentage of certain key tests that were verified before a specific time on the phlebotomy day. A weighted mean synthetic indicator was also designed. They were calculated for inpatients at 15:00 and 12:00 and for primary care patients only at 15:00. The troponin TAT of emergency department patients, calculated as the difference between the troponin verification and registration time, was selected as the stat laboratory TAT indicator. Results: The routine and stat TAT improved along the 10-year study period. The synthetic indicator showed the same trend. Conclusions: The implementation of systematic and continuous monitoring over years, promoted a continuous improvement in TAT which will probably benefit patient outcome and safety.